Analisis Pengetahuan Pelaku UMKM Tentang Produk Halal di Kelurahan Cijagra - Munadi, Muhammad Nadzir Al; Gusnadi, Dani (Ikatan Da'i Indonesia, 2024)
This study aims to measure and analyze the level of MSME actors in business around the Cijagra village with a focus on the target research object, namely on UMKM business actors in the Cijra Agra village. The research method used is a qualitative approach method by interviewing business actors and documenting one of the shopkeepers. As for displaying the results of the field in the UMKM business in the village of Cijagra. The data is analyzed using data collection techniques with an interview method approach using sample data and processed into concrete and relevant data. The results of the discussion in this study are expected to be a little insight into the UMKM actors around the Cijagra village.